Factors Other Than Skull Density Ratio Affect Treatment Outcomes in MR-Guided Focused Ultrasound for Tremor. (16th November 2020) - Katlowitz, Kalman; Rozman, Peter; Pourfar, Michael; Mogilner, Alon Y
Abstract: INTRODUCTION: Successful clinical outcomes in MRI-guided focused ultrasound (MRgFUS) thalamotomy for the treatment of tremor rely on proper patient selection. Current guidelines suggest selecting patients with a skull density ratio (SDR) > 0.4, yet some reports suggest that this is neither sufficient nor necessary for a successful treatment. We have similarly observed both treatment failure as well as transient or incomplete clinical improvement in patients who qualified for MRgFUS by classic selection guidelines. METHODS: We retrospectively reviewed patients who underwent MRgfUS thalamotomy for tremor at our institution from 8/2018 to 2/2020. We evaluated anatomical parameters derived from the preoperative CT scan and correlated these with intra-operative physical measures and clinical tremor outcomes at a minimum follow-up of 3 weeks. RESULTS: Of the 30 patients we evaluated, 3 did not achieve lesional maximum temperatures (maxT) of 55°C despite having an SDR above the recommended threshold. We found no correlation between SDR and maxT or heating efficiency (E). In contrast, we did find a significant ( P < .01) negative correlation between skull thickness (ST) and maxT (r 2 = 0.67) as well as ST and E (r 2 = 0.43). Additionally, by considering the ST in conjunction with the SDR, skull area, and average skull density, we were able to predict the maxT within 2 degrees in greater than 83% of patients using a linear model. Notably, we found that patients taking medications for osteoporosis had a significantly higher rate of failing to reach 55C (66% vs 4%, P = .02), likely related to their significantly higher skull thickness (9.0 vs 6.5mm, P = .001). However, we did not find a significant association between SDR, ST, or the maxT and subjective tremor or overall outcomes (p>0.10 for all). CONCLUSION: Above the recommended threshold, SDR provided no further predictive value for the success of MRgFUS. Additionally, preoperative planning should account for mean skull thickness and concurrent medications, as patients with values above 9mm or those taking mineralization-modifying medications might not experience optimal outcomes. Further understanding of these parameters is needed to better refine our patient selection process and pre-operative planning.